2003
DOI: 10.2337/diabetes.52.2.558
|View full text |Cite
|
Sign up to set email alerts
|

The C-174G Promoter Polymorphism of the IL-6 Gene Affects Energy Expenditure and Insulin Sensitivity

Abstract: 1Interleukin-6 (IL-6) is a pleiotropic cytokine expressed in many tissues. IL-6 null mice show low energy expenditure, but the effect of the variants of the IL-6 gene on energy expenditure has not been previously studied in humans. Therefore, we investigated the effect of the C-174G promoter polymorphism of the IL-6 gene on energy expenditure, measured by indirect calorimetry in healthy Finnish subjects (n ‫؍‬ 124). We also measured insulin sensitivity by the hyperinsulinemic-euglycemic clamp. Subjects with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
7
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 25 publications
5
80
7
5
Order By: Relevance
“…However, our findings are supported by recent evidence that energy expenditure and body temperature are lower in the À174 CC genotype in healthy male and female subjects. 14,31 Altogether, this indicates that our finding is not coincidental although further studies are needed to investigate if these results can be applied to random samples of a population. It also remains to be investigated whether the effect of the À174 G/ C genotype on overweight risk is confined to certain populations.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, our findings are supported by recent evidence that energy expenditure and body temperature are lower in the À174 CC genotype in healthy male and female subjects. 14,31 Altogether, this indicates that our finding is not coincidental although further studies are needed to investigate if these results can be applied to random samples of a population. It also remains to be investigated whether the effect of the À174 G/ C genotype on overweight risk is confined to certain populations.…”
Section: Discussionmentioning
confidence: 82%
“…[27][28][29] Moreover, endogenous IL-6 seems to influence energy expenditure during exercise. 30 Interestingly, the data of recent studies indicate that the -174 C allele is associated with decreased energy expenditure 31 and slightly decreased body temperature. 14 Taken together, these results indicate that the À174 C allele of the IL-6 promoter decreases IL-6 production, which in turn results in decreased energy expenditure and accumulation of body fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…177 Furthermore, the CÀ174C genotype has been associated with lower energy expenditure and lower rate of whole-body glucose uptake. 178 Another IL6 polymorphism, a CA repeat, has in two independent populations been reported to be associated with obesity. 179 Furthermore, polymorphisms in the IL6 receptor (IL6R) have been reported to be associated with obesity in Pima Indians and a Spanish population.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…Furthermore, a recent study showed that mice completely lacking IL-6 became obese and that intracerobroventricular injection of IL-6 increased energy expenditure (31). An association between energy expenditure, insulin sensitivity, and the C174G polymorphism of the IL-6 promoter was also recently reported (32).…”
mentioning
confidence: 99%